Body mass index and sex differences for mortality in hospitalized COVID-19 patients: a path analysis using a brazilian national database - Erika Cardoso dos Reis; Elma Lúcia de Freitas Monteiro; Joilson Meneguci; Phillipe Rodrigues; Alexandre Palma; Jair Sindra Virtuoso Junior; Sonia Regina Lambert Passos; Maria Angelica Borges dos Santos (BMC, 2023)
Abstract Previous studies have shown that associations between obesity and other comorbidities favor worse outcomes in COVID-19. However, it is not clear how these factors interrelate and whether effects on men and women differ. We conducted an observational, cross-sectional study using a national COVID-19 inpatient database. We studied differences in direct and indirect effects of obesity and comorbidities according to sex and body mass index (BMI) categories in hospitalized COVID-19 patients in Brazil using path analysis models and logistic regression. For men, path analysis showed a direct association between BMI and death and a negative correlation of death and chronic cardiovascular disease (CCD). For women, the association of BMI and death was indirect, mediated by admission to the ICU and comorbidities and association with CCD was non-significant. In the logistic regression analyses, there was a positive association between death and BMI, age, diabetes mellitus, kidney and lung diseases and ICU admission. We highlight the need to consider the distinct impact of obesity and sex on COVID-19, of monitoring of BMI and of the design for specific male-targeted approaches to manage obesity.